Cocoa cycles - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Cocoa cycles: the economics of cocoa supply edited by François Ruf and P S Siswaputranto 1995 384pp ISBN 1 85573 215 7